The Role Of Symbolism In Postmodern Literature - Sadikova Dildora Nizomovna (Zien Journals, 2021)
By contrasting its application with previous literary trends and examining how postmodernist writings use symbols to question meaning, identity, and narrative authority, this essay examines the function and evolution of symbolism in postmodern literature. This study shows how symbolism in postmodernism becomes a tool for challenging reality, upending interpretation, and expressing cultural disintegration through an analysis of important postmodern works and theoretical viewpoints
Keywords: postmodernism; symbols